Identifikasi Resiko dan Penerapan Metode 6S pada Lingkungan Kerja di Roz Collection Pabelan - Wicaksono, Aditya Rangga; Rianto, Rianto; Setiawan, Nicko Kurnia; Anggraini, Intan Ariesta; Putra, Yanuar Surya (Fokus ABDIMAS, 2024)
In running a business, of course, you will face risks. The risks that arise come from the work environment, one of which is related to occupational safety and health. Observations made in this service found that there are still non-conformities with workplace standards and there are tools with certain risks that have not been equipped with occupational health safety equipment. This service aims to identify risks, know the impacts caused, and to find out the actions that need to be taken as prevention of risks arising in the work environment of Roz Collection Pabelan MSMEs. This activity is divided into 3 stages, namely, (a) observation and risk identification, (b) cleaning, structuring, and labelling workplaces, and (c) education about occupational safety and health for employees. This activity assists owners in adjusting workplace standardization according to the 6S method and worker risk management with the implementation of occupational safety and health at MSMEs Roz Collection Pabelan. Keywords : 6S, Identifikasi resiko, lingkungan kerja,